تحضير ودراسة الأغشية الرقيقة لكبريتيد الرصاص (PbS) المحضرة بطريقة الحمام الكيميائي - سعدالله, فطيمة (University of eloued جامعة الوادي, 2018)
تم في هذا العمل تحضير ودراسة الأغشية الرقيقة لكبريتيد الرصاص (PbS)المرسبة بتقنية الحمام الكيميائي على ركائز زجاجية. يحتوي محلول الترسيب على نترات الرصاص والثيوريا، مع إضافة معقد ثلاثي الايثانول-أمين. العينات المحضرة رتبت إلى سلسلتين وفقا لشروط الترسيب والمتمثلة في: زمن الترسيب (30-90)minودرجة حرارة الترسيب .( 55-90)°C بالنسبةللسلسلة الأولى: أظهرت نتائج تشخيص الأشعة السينية (X) أن شرائح PbSالمحضرة ذات بنية مكعبة وفق الاتجاه التفضيلي (200). أبدت النفاذية الضوئية تناقصا مع مرورالزمن إلى غاية 60min)) وتزايدا عند (min90), قيم الفاصل الطاقي تتناقص من القيمةev) 2.00(إلى غايةev)1.63( ثم تزداد عندmin) 90) إلى القيمة0ev) 1.7(. بالنسبة للسلسلة الثانية: فقد أظهر إنعراج الأشعة السينية نقصان في شدة القمة (200) بزيادة درجة حرارة الترسيب يرافقه زيادة في شدة القمة (111) والتي تكون بشدة أكبرعند °C)90). أما النفاذية الضوئية فقد أبدت تناقصا بزيادة درجة حرارة الترسيب. كما لوحظ تناقص في قيم الفاصل الطاقيبنسب معتبرة. In this work, elaboration and characterizationof lead sulfide thin films (PbS) on glass substrates were done, these films wereprepared by chemical bath deposition technique. In this study, two sets of samples were prepared, in each set only one parameter is varied while the rest of parameters were fixed.The deposition solution contains lead nitrate and thioureaas source of lead and sulphur respectively, triethanolamine wasused as complexing agent.In the first set, the depostion time is varied from 30 to 90 min, while in the second the bath temperature is changed from 55 to 90 °C. For the first set,cubic PbS thin filmswere obtained with (200) preferred orientation. With increase in deposition time to 60 min the transmittance decreased and at 90 minincreased, the values ofthe optical band gap decreases from 2.00to 1.63 evand increased at 90 min to 1.70 ev value.The FT-IR measurements showed the appearance of the Pb-S bond at 477.68 cm-1 . For the second set, X-ray diffraction showed a decrease of the intensity of the peak (200) and an increase of the intensity of the peak (111) with increased bath temperature. With increase in bath temperature thetransmittancedecreasesand the energy band gap decreases too
مذكرة ماسترتخصص فيزياء
Keywords: : كبريتيد الرصاص، الترسيب بالحمام الكيميائي، الأغشية الرقيقة، إنعراج الأشعة السينية، (FT-IR).; lead sulfide (PbS), chemical bath deposition (CBD), thin films, XRD, FTIR